Evasion of maternal antibody protection by an IBDV Argentine variant - Jaton, Juan Marcelo; Gomez, Evangelina Raquel; Lucero, Maria Soledad; Rizzi, Lucia; Gravisaco, María José; Pinto, Silvina; Berinstein, Analia; Chimeno Zoth, Silvina Andrea (Elsevier, 2024)
Infectious bursal disease (IBD) is a viral disease that affects the ability of chickens to produce humoral immune responses. One way to prevent the disease is the passage of maternally derived antibodies (MDA) from dams to offsprings via the yolk. Despite sanitary measures, which include immunization with genogroup 1 (G1) vaccines, infections with IBDV genogroup 4 (G4) in young animals have been detected. The aim of this study was to determine whether a local IBDV isolate belonging to G4 could evade the immunity generated by MDAs. Twelve-day-old animals positive for MDA, were inoculated with G1 or G4 isolates or phosphate buffered saline (PBS) as a control. After 1 wk, the animals were sacrificed and the following parameters were evaluated: bursa-body (BB) ratio, viral load, and histologic damage in the bursa of Fabricius. Results showed that G4-infected animals had significant differences in the BB ratio compared to the PBS group. In addition, viral load was significantly higher in the G4 group than in the G1 group. Histologic damage in the bursa of Fabricius was detected only in G4-infected MDA chickens. Our results suggest that infection with G4 local isolate can circumvent the immunity generated by MDA and, furthermore, that G4 isolate does not differ in its pathogenicity from G1 isolate, which underlines the need to include variant strains in vaccine formulations to reduce potential losses caused by these viruses.